Democracy promotion and China: blocker or bystander? - Chen, Dingding; Kinzelbach, Katrin (Democratization, 2015)
The increasingly prosperous, mighty, and assertive China is arguably the most powerful country blocking democracy today. In addition to withholding democratic rights of one-fifth of the world's population, authoritarian China represents an alternative development model that has gained significant traction. China thus constitutes a challenge to democracy promoters. But does Beijing also countervail democracy promotion by the European Union and the United States? After a summary of the party-state's response to democracy promotion at home, we test the hypothesis that geostrategic interests or a perceived risk of regime survival will lead the People's Republic to countervail democracy promotion outside its own borders. We do so by focusing on the most likely cases in China's near-abroad: Myanmar and Hong Kong. Our analysis of Myanmar suggests that Beijing remains focused on securing economic and security interests irrespective of regime type when regime survival at home is not at risk. The case of Hong Kong, on the other hand, allows us to identify the tactics used by Beijing when there is a significant risk of democratic spillover. This case also demonstrates that the People's Republic of China is able to stifle United States and European Union democracy support when it wishes to do so.
CRIS-Team Scopus Importer:2023-03-21
Keywords: autocracy; China; democracy; Hong Kong; human rights; Myanmar